Knowledge, Attitudes, and Practices Toward COVID-19 Among Chinese Teachers, Shenzhen: An Online Cross-sectional Study During the Global Outbreak of COVID-19 - Chen, Hongbiao; Zhang, Minyi; Su, Lixian; Cao, He; Zhou, Xiaofeng; Gu, Zihao; Liu, Huamin; Wu, Fei; Li, Qiushuang; Xian, Juxian; Chen, Qing; Lin, Qihui (Frontiers in Public Health, 2021)
Background: Adequate understanding and precautionary behaviors are of vital importance to contain the spread of COVID-19. To date, the knowledge, attitudes, and practices (KAP) towards COVID-19 among different populations have been reported, while such information is unavailable in teachers. We aimed to investigate the teachers’ KAP associated with COVID-19 during the global outbreak. Methods: A large-scale population-based survey was conducted to gather information on COVID-19-related KAP among Chinese teachers using a self-administered questionnaire. We received 10,658 responses in April 2020, out of which 8248 were enrolled in the final analysis. Participants responded to a self-administered questionnaire concerning demographic characteristics and KAP associated with COVID-19. Results: This study included 4252 (51.6%) teachers in kindergartens, 2644 (32.1%) teachers in primary schools, and 1352 (16.4%) teachers in secondary schools. The knowledge level (mean: 4.46 out of 7 points) was relatively lower than the levels of attitudes (mean: 3.27 out of 4 points) and practices (mean: 4.29 out of 5 points) towards COVID-19. Knowledge scores significantly varied by the collected demographic variables except education worksite (P < 0.05), while practice scores significantly differed in age groups (P < 0.05), education level (P < 0.001), education worksite (P < 0.001), and years of teaching (P < 0.001). The multivariate logistic analysis indicated that poor knowledge related to COVID-19 was common among male, younger, and less-educated teachers. In contrast, female teachers and those with higher education levels tend to have good practices against COVID-19. Conclusion: The present study suggested the knowledge gaps regarding COVID-19 were needed to be corrected immediately in teachers. Given the critical role of teachers in the education system, health authorities should take gender, age, and education level into account when developing suitable health interventions.